Growth performance and competitiveness of finfish and frozen shrimp exports in Sri Lanka - Bandara, Tharindu; Abeywickrama, L. M.; Radampola, K. (Indian Journal of Fisheries, 2020)
Frozen shrimp and finfish are important export products in Sri Lankan economy. Careful evaluation of growth trends and competitiveness of these products is important in further value chain development and sustainable economic profits. The present study examined the growth performance and export competitiveness of frozen shrimp and major finfish exports from Sri Lanka during 2000-2015. Analysis of finfish exports showed that bigeye tuna (Thunnus obesus) and yellowfin tuna (Thunnus albacares) were dominant export products. Compound growth rate analysis (CGR) of frozen shrimp indicated that there was a negative growth rate in terms of both export value (-9.3%) and export quantity (-9.07%) during 2000-2015. Fresh chilled fish, frozen fish and fish fillet and other meat have shown positive growth rates in export value (5.09, 10.24 and 70.10% respectively). However, considerable instability (11.07 and 11.74 in terms of value and quantity) was recorded in fish fillet and other meat. Export competitiveness index (XCl) for fresh/chilled fish, frozen fishand fish fillet showed positive competitiveness (XCl>1) during 2001-2015. Revealed comparative advantage (RCA) for finfish exports have shown strong competitiveness (RCAâ‰¥ 4) during 2000-2015. Frozen shrimp exports were weakly competitive (1